White holes - Rovelli, Carlo, 1956- (Riverhead Books, 2023)
"Let us journey, with beloved physicist Carlo Rovelli, into the heart of a black hole. We slip beyond its horizon and tumble down this crack in the universe. As we plunge, we see geometry fold. Time and space pull and stretch. And finally, at the black hole's core, space and time dissolve, and a white hole is born. Rovelli has dedicated his career to uniting the time-warping ideas of general relativity and the perplexing uncertainties of quantum mechanics. In White Holes, he reveals the mind of a scientist at work. He traces the ongoing adventure of his own cutting-edge research, investigating whether all black holes could eventually turn into white holes, equally compact objects in which the arrow of time is reversed. Rovelli writes just as compellingly about the work of a scientist as he does the marvels of the universe. He shares the fear, uncertainty, and frequent disappointment of exploring hypotheses and unknown worlds, and the delight of chasing new ideas to unexpected conclusions. Guiding us beyond the horizon, he invites us to experience the fever and the disquiet of science-and the strange and startling life of a white hole"--